The Swiss family Robinson - James, Raymond; Wyss, Johann David, 1743-1818.; Beier, Ellen (India : Madhuban educational books, 1999)
Relates the fortunes of a shipwrecked family as they imaginatively adapt to life on an island with abundant animal and plant life.
Keywords: Survival -- Fiction; Family life -- Fiction; Islands -- Fiction